Host-Guest Interactions Between Metal–Organic Frameworks and Air-Sensitive Complexes at High Temperature - Huang, Bo; Tan, Zhe (Frontiers in Chemistry, 2021)
The host-guest chemistry of metal–organic frameworks (MOFs) has been attracting increasing attention owing to the outstanding properties derived from MOFs-guests combinations. However, there are large difficulties involved in the syntheses of the host-guest MOF systems with air-sensitive metal complexes. In addition, the behaviors on host-guest interactions in the above systems at high temperature are not clear. This study reported the synthetic methods for host-guest systems of metal–organic framework and air-sensitive metal complexes via a developed chemical vapor infiltration process. With the synchrotron X-ray powder diffraction (XRPD) measurements and Fourier Transform infrared spectroscopy (FTIR), the successful loadings of Fe(CO)5 in HKUST-1 and NH2-MIL-101(Al) have been confirmed. At high temperatures, the structural and chemical componential changes were investigated in detail by XRPD and FTIR measurements. HKUST-1 was proven to have strong interaction with Fe(CO)5 and resulted in a heavy loading amount of 63.1 wt%, but too strong an interaction led to deformation of HKUST-1 sub-unit under heating conditions. NH2-MIL-101(Al), meanwhile, has a weaker interaction and is chemically inert to Fe(CO)5 at high temperatures.